Eksplorasi Tumbuhan Obat Pada Ketinggian 1400-1600 m. Dpl Di Kawasan Hutan Alam Girimanik Setren Kecamatan Slogohimo Wonogiri - ANNOFI KUSUMA, NELA; Suryani, M.Sc., Dra. Titik (2016)
Natural Forest Girimanik one of the forests have flora diversity including medicinal plants. The purpose of this study was to determine the species of medicinal plants at an altitude of 1400-1600 asl. in the Natural Forest district Girimanik. The research method used purposive sampling exploration and method of plotless transect. The results showed that there are 10 order, 10 families, 17 genera that are include 17 species of medicinal plants are spread at an altitude of 1400 asl. - 1600 asl. Family types of medicinal plants are found at an altitude of 1400 asl - 1600 asl are Umbeliferae, Poaceae, Rubiaceae, Verbenaceae, Papilionaceae, Polygalaceae, Malvaceae, Compositae, Melastomaceae, and woodsiaceae. Medicinal plant species founded are Centella asiatica, Paspalum scrobiculatum, Ischaemum T'timorense, Sporobolus poiretii, Stachytarpheta jamaicensis, Diplazium sibiricum, Axonopus compressus, Urena lobata, Melastoma sp., Oplismenus burmanni, Bidens pilosa, Polygala paniculata, Borreria alata, Centrosema molle, and Eupatorium riparium, Lantana camara, and Imperata cylindrica.